TO DETERMINE CUT OFF OF FERTILITY PROFILE OF PATIENTS WITH ANDROGEN INSENSITIVITY SYNDROME (AIS) AT DIFFERENT AGES IN PAKISTANI POPULATION - Hanif, Waqas; Asif, Naveed; Younas, Muhammad; Haroon, Zujaja Hina; Ain, Qurat Ul; ., Noreen (Pakistan Armed Forces Medical Journal, 2020)
Objective: Current study was aimed to determine cut off value of fertility profile in patients with Androgen Insensitivity Syndrome (AIS) presented at different ages tertiary care hospital of Rawalpindi, Pakistan. Study Design: Cross sectional study.Place and Duration of Study: Department of Chemical Pathology and Endocrinology, Armed Forces Institute of Pathology (AFIP) Rawalpindi, from Jan 2016 to Dec 2017.Methodology: Ninety-one (91) patients diagnosed as cases of AIS were included in the study. Subjects were consecutively selected as per inclusion and exclusion criteria. Blood samples were collected from each subject for basal serum testosterone, serum luteinizing hormone (LH) and serum follicular stimulating hormone (FSH) level. Human chorionic gonadotropins (hCG) stimulation test was performed in each subject as per laid down protocol. Sandwich chemiluminescence immunoassay technique was used to analyze serum testosterone, LH and FSH. Serum dihydrotestosterone was also analyzed to calculate testosterone and dihydrotestosterone (T/DHT) ratio. Results: Mean age of subjects was 1.78 ± 0.95 years. Cut off values of serum LH (IU) according to age in patients with AIS are; 6.80 (1 day to 1 year), 6.74 (1 year to 10 years) 6.6 (10 years to onward), serum FSH (IU) 9.71 (1 day to 1 year), 9.01 (1 year to 10 years), 10.01 (10 years to onward), serum testosterone (ng/dl) 107.32 (1 day to 1 year), 120.76 (1 year to 10 years), 98.32 10 years to onward) before and 310.39 (1 day to 1 year), 354.71 (1 year to 10 years), 293.43 (10 years to onward) after hCG, serum..........